Approaches and Strategies for Character Education for Santri at the AI ​​Riyadloh Islamic Boarding School, Semarang Regency - Rizky Maulana Aziz; Badrus Zaman (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2023)
The objective of this research is to identify optimal methods for suitably imparting character education. The data-gathering methods employed in this research encompass observation, interviews, and documentation. Triangulation serves as a method to assess the accuracy and reliability of the acquired data. Data analysis was conducted via data reduction methodologies, data visualization, and inference drawing. The research findings indicate that character education at the API Al Riyadloh Islamic Boarding School employs two distinct approaches: a teacher-centered approach and a student-centered approach. In a teacher-centered method, the instructor assumes an active position as an authoritative figure who is revered and obeyed by pupils based on the teachings found in the texts being taught. Conversely, a student-centered approach promotes the active participation of students in structured nighttime learning activities. In addition to that, the API Al Riyadloh Islamic Boarding School employs six ways to cultivate the students' character. The tactics encompass habituation, cultivation, acquiring knowledge of positive attributes, experiencing and cherishing positivity, engaging in virtuous activities, emulating positive influences from the environment, and seeking repentance. These tactics aim to cultivate students' familiarity with kindness, comprehension of moral principles, emotional connection to and appreciation for kindness, and active engagement in virtuous deeds